Formare al futuro Progettualità, metodi e innovazione - Selmo, Laura (Educazione per tutta la vita, 2022)
Starting from an analysis around the relationship between individual, training and self-realization, the book is focused on the pedagogical dimension of work within organizations and on the methodological tools that training should offer to face the future. In particular, the first part reflects on the importance of training within working contexts, with particular attention to the strategic role of the development of human resources and the importance to recognize individuals' peculiarities and abilities. The second part is focused on the methodological tools of training that can be used to orient towards new future perspectives and to develop professional and personal skills. This book is aimed at HR trainers, HR consults and managers.